2018
DOI: 10.1016/j.eats.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Dynamic Snapping Biceps Femoris Tendon

Abstract: A snapping biceps tendon is an infrequently seen and commonly misdiagnosed pathology, leaving patients with persistent symptoms that can be debilitating. Patients will present with a visible, audible, and/or painful snap over the lateral aspect of their knee when performing squats, sitting in low seats, or participating in activities with deep knee flexion. A thorough knowledge of the anatomy is essential for surgical treatment of this pathology, which is caused by a detachment of the direct arms of the long a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Pain and snapping from the biceps femoris insertion can be due to anomalous anatomy of the insertion itself, dysmorphia of the fibular head or from trauma. 3 10 11 12 13 14 Saltzman et al also reported that the popliteus tendon, lateral collateral ligament, and iliotibial band can cause a popping sensation and snapping at the lateral knee. 15…”
Section: Discussionmentioning
confidence: 99%
“…Pain and snapping from the biceps femoris insertion can be due to anomalous anatomy of the insertion itself, dysmorphia of the fibular head or from trauma. 3 10 11 12 13 14 Saltzman et al also reported that the popliteus tendon, lateral collateral ligament, and iliotibial band can cause a popping sensation and snapping at the lateral knee. 15…”
Section: Discussionmentioning
confidence: 99%
“…Several previous case reports described this phenomenon. Biceps femoris tendon syndrome has been found to be due to anomalous insertion of the long head of the biceps femoris tendon [ 1 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], fibular head deformity [ 15 , 16 , 17 , 18 ], tendon injury [ 19 , 20 ], and normal anatomy without trauma [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bagchi and Grelsamer and Kristen et al described abnormal anterior insertion on proximal tibia treated by partial fibular head resection. [ 7 , 9 ] Date et al, Matar and Farrar, Kissenberth and Wilckens, Kennedy et al, and Reid and Mofidi described abnormal insertion of the biceps femoris treated by release and reinsertion of the tendon in the fibular head [ 3 , 8 , 11 , 13 , 14 ]. Ernat and Galvin described abnormal anterior insertion on proximal tibia and thickened anterolateral fibular insertion treated only with release of the abnormal tendon insertion [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPN neurolysis, including 5-7 mm of release of the peroneus longus fascia overlying the nerve, is usually performed to minimize trauma to the nerve caused by swelling and stretching. [59]…”
Section: Chronic Management Of Multiple Ligament Injuriesmentioning
confidence: 99%